Comparative effectiveness of antitumour necrosis factor agents, biologics with an alternative mode of action and tofacitinib in an observational cohort of patients with rheumatoid arthritis in Switzerland. Issue 1 (7th May 2020) - Finckh, A; Tellenbach, C; Herzog, L; Scherer, A; Moeller, B; Ciurea, A; von Muehlenen, I; Gabay, C; Kyburz, D; Brulhart, L; Müller, R; Hasler, P; et al.
Abstract : Background: Multiple biologic and targeted synthetic disease-modifying rheumatic drugs (b/tsDMARDs) are approved for the management of rheumatoid arthritis (RA), including TNF inhibitors (TNFi), bDMARDs with other modes of action (bDMARD-OMA) and Janus kinase inhibitors (JAKi). Combination of b/tsDMARDs with conventional synthetic DMARDs (csDMARDs) is recommended, yet monotherapy is common in practice. Objective: To compare drug maintenance and clinical effectiveness of three alternative treatment options for RA management. Methods: This observational cohort study was nested within the Swiss RA Registry. TNFi, bDMARD-OMA (abatacept or anti-IL6 agents) or the JAKi tofacitinib (Tofa) initiated in adult RA patients were included. The primary outcome was overall drug retention. We further analysed secondary effectiveness outcomes and whether concomitant csDMARDs modified effectiveness, adjusting for potential confounding factors. Results: 4023 treatment courses of 2600 patients were included, 1862 on TNFi, 1355 on bDMARD-OMA and 806 on Tofa. TNFi was more frequently used as a first b/tsDMARDs, at a younger age and with shorter disease duration. Overall drug maintenance was significantly lower with TNFi compared with Tofa [HR 1.29 (95% CI 1.14 to 1.47)], but similar between bDMARD-OMA and Tofa [HR 1.09 (95% CI 0.96 to 1.24)]. TNFi maintenance was decreased when prescribed without concomitant csDMARDs [HR: 1.27 (95% CI 1.08 to 1.49)], while no difference was observed for bDMARD-OMA or Tofa maintenance with respect to concomitant csDMARDs. Conclusion: Tofa drug maintenance was comparable with bDMARDs-OMA and somewhat higher than TNFi. Concomitant csDMARDs appear to be required for optimal effectiveness of TNFi, but not for bDMARD-OMA or Tofa.